Metaphors of 'Worldly Life' and 'Hereafter' in the Holy Quran: A Conceptual Approach - Abid Saleh, Aziz Khalaf; Hussein Khader, Malak Hassan (Thi Qar Arts Journal, 2025)
Conceptual Metaphor is a theory that is associated with cognitive semantics, in which metaphor is seen as a process of understanding one conceptual domain in terms of another. The present study focuses on the cognitive metaphorical uses of some expressions that talk about  the Worldly Life (ٱلْحَيَوٰةَ ٱلدُّنْيَا)  and the Hereafter (  الآخرة) in the Holy Quran. An electronic research has been made for only the verses that contain the expressions ‘the Worldly Life’ (ٱلْحَيَوٰةَ ٱلدُّنْيَا)  and  ‘the Hereafter’ ( الاخرة) in the Holy Quran. Lakoff and Johnson’s (1980) model of Conceptual Metaphor Theory is adopted for the analysis of the Quranic verses. The Quranic texts under study are translated into English, as the first procedure, before they are analyzed by the aid of  Lakoff and Johnson’s (1980) Conceptual Metaphor Theory. There is a tendency by the Holy Quran to make a conceptual  mapping between the concept of ‘Worldly Life’ and the concepts of being 'worldly,' 'trivial,' 'temporary,' 'short-living,' etc. Whereas the conceptual mapping is to be made between the concept of the ‘Hereafter’ and the concepts of being 'heavenly,' 'precious,' 'constant,' 'ever-lasting,' etc.